INDONESIAN LANGUAGE EDUCATION POLICY IN RELATION TO THE NATIONAL EDUCATION GOALS: A THEORETICAL PERSPECTIVE - Santi Mayasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
Education plays an important role for the quality of human’s life. Education is a process of accommodating learners to develop their potential based on the talent and ability they have. Through this process, individuals will have a better personality, IQ, manner, religious belief. Indonesian language in an education setting supports the process of gaining knowledge because this is considered as a carrier of knowledge, a means of communicating ideas, thought, and feeling, and a means of increasing nationality among individuals whole over Indonesia. By having this, Indonesian language education policy is considered as a means of gaining national education goals. However, the role of stakeholders and society is undeniable. They can protect and develop the position of Indonesian language and they can accommodate the attainment of national education goals.Key Words: Education, Indonesian Language, Policy, National Education Goals, Stakeholders